2010
DOI: 10.1057/jibs.2009.88
|View full text |Cite
|
Sign up to set email alerts
|

From the Editors: Common method variance in international business research

Abstract: JIBS receives many manuscripts that report findings from analyzing survey data based on same-respondent replies. This can be problematic since samerespondent studies can suffer from common method variance (CMV). Currently, authors who submit manuscripts to JIBS that appear to suffer from CMV are asked to perform validity checks and resubmit their manuscripts. This letter from the Editors is designed to outline the current state of best practice for handling CMV in international business research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
1,857
0
26

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,814 publications
(1,899 citation statements)
references
References 16 publications
16
1,857
0
26
Order By: Relevance
“…To reduce the potential common method bias, we followed Podsakoff et al's (2012) suggestion to organize the data collection process to ensure the anonymity and confidentiality of the responses, emphasizing that there are no right or wrong answers, and covering the items relating to the predictor variables before those relating to the outcome variables. Furthermore, following the suggestions of Chang et al (2010) and Podsakoff et al (2003), we used multiple statistical remedies to ensure that common method v 2 Chi-Square, df degree of freedom, CFI comparative fit index, RMSEA root mean square error of approximation, SAMR social alliance management routines, MT mutual trust, RE relational embeddedness, RC relational commitment, SAP social alliance performance, SARBM social alliance relationship-building motive, SABEM social alliance benefits-exploiting motive bias is not an issue for this study. First, we performed Harman's single-factor test by subjecting all of the items in our study to exploratory factor analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the potential common method bias, we followed Podsakoff et al's (2012) suggestion to organize the data collection process to ensure the anonymity and confidentiality of the responses, emphasizing that there are no right or wrong answers, and covering the items relating to the predictor variables before those relating to the outcome variables. Furthermore, following the suggestions of Chang et al (2010) and Podsakoff et al (2003), we used multiple statistical remedies to ensure that common method v 2 Chi-Square, df degree of freedom, CFI comparative fit index, RMSEA root mean square error of approximation, SAMR social alliance management routines, MT mutual trust, RE relational embeddedness, RC relational commitment, SAP social alliance performance, SARBM social alliance relationship-building motive, SABEM social alliance benefits-exploiting motive bias is not an issue for this study. First, we performed Harman's single-factor test by subjecting all of the items in our study to exploratory factor analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We are also aware of the potential common method bias as reported by Chang et al (2010) and the need to perform validity checks. However, during the study we were unable to gather additional data to address this issue.…”
Section: Testing the Role Of Pro-innovation Organisational Culturementioning
confidence: 99%
“…This is a concern in our study as we used a self-reported questionnaire in which independent and dependent variables were captured at the same time (Podsakoff & Organ, 1986). A preferred way of dealing with common method variance is to capture dependent variable(s) from a separate source (Chang, van Witteloostuijn & Eden, 2010;Podsakoff, MacKenzie, Lee, & Podsakoff, 2003). For reasons of practicality and concerns about the reliability and comparability of company sources containing information representing internal knowledge flows, we were not able to do this.…”
Section: Data Quality and Analysismentioning
confidence: 99%